ROS-mediated plasmodesmal regulation requires a network of an Arabidopsis receptor-like kinase, calmodulin-like proteins, and callose synthases - Vu, Minh Huy; Hyun, Tae Kyung; Bahk, Sungwha; Jo, Yeonhwa; Kumar, Ritesh; Thiruppathi, Dhineshkumar; Iswanto, Arya Bagus Boedi; Chung, Woo Sik; Shelake, Rahul Mahadev; Kim, Jae-Yean (Frontiers in Plant Science, 2023)
Plasmodesmata (PD) play a critical role in symplasmic communication, coordinating plant activities related to growth & development, and environmental stress responses. Most developmental and environmental stress signals induce reactive oxygen species (ROS)-mediated signaling in the apoplast that causes PD closure by callose deposition. Although the apoplastic ROS signals are primarily perceived at the plasma membrane (PM) by receptor-like kinases (RLKs), such components involved in PD regulation are not yet known. Here, we show that an Arabidopsis NOVEL CYS-RICH RECEPTOR KINASE (NCRK), a PD-localized protein, is required for plasmodesmal callose deposition in response to ROS stress. We identified the involvement of NCRK in callose accumulation at PD channels in either basal level or ROS-dependent manner. Loss-of-function mutant (ncrk) of NCRK induces impaired callose accumulation at the PD under the ROS stress resembling a phenotype of the PD-regulating GLUCAN SYNTHASE-LIKE 4 (gsl4) knock-out plant. The overexpression of transgenic NCRK can complement the callose and the PD permeability phenotypes of ncrk mutants but not kinase-inactive NCRK variants or Cys-mutant NCRK, in which Cys residues were mutated in Cys-rich repeat ectodomain. Interestingly, NCRK mediates plasmodesmal permeability in mechanical injury-mediated signaling pathways regulated by GSL4. Furthermore, we show that NCRK interacts with CALMODULIN-LIKE PROTEIN 41 (CML41) and GSL4 in response to ROS stress. Altogether, our data indicate that NCRK functions as an upstream regulator of PD callose accumulation in response to ROS-mediated stress signaling pathways.